Prototype Development, Usability, and Preference of a Culturally-relevant Pictorial Aid to Facilitate Comprehension of Likert-type Levels of Agreement in Caregivers of Children Living With HIV in Ghana - Kusah, J.T.; Ramos, S.R; Paintsil, E.; Ofori-Atta, A.; Amissah, K.A.; Alhassan, A.; Ofori, I.P.; Reynolds, N.R. (Computers, Informatics, Nursing, 2020)
Pictorial illustrations of Likert-type scales are culturally useful and may reduce error associated with usage of Westernized self-report measures in low- and middle-income countries. Pictorial illustrations can be encounter-specific decision aids in populations with low literacy or English proficiency. In an unanticipated finding from the SANKOFA study, caregivers of children living with human immunodeficiency virus experienced challenges comprehending Likert-type scales. A cross-sectional, qualitative study was conducted with a SANKOFA participant subset (n = 30) in Ghana. Using an informatics-based formative design approach, we developed a culturally-relevant pictorial aid to assess usability and preference when compared to a Likert-type self-report measure. Ninety percent (n = 27) of substudy participants preferred the pictorial of a traditional Bolga basket over a shallow basket. Forty-three percent (n = 13) preferred the pictorial aid over the Likert-type measure. Fifty percent reported the pictorial aid was easy to use. Fifty-seven percent preferred the Likert-type measure, potentially because English proficiency is regarded in Ghana as a means of upward social and financial mobility. Such cultural norms may have contributed to the lack of consensus and must be considered for pictorial aids to be meaningful. Pictorial aids have been designed for use in clinical and research settings. They reduce barriers associated with lower textual literacy while facilitating comprehension and decision-making.
Research Article
Keywords: SANKOFA; informatics-based; Ghana; financial mobility